2015
DOI: 10.3102/0013189x15580314
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Rain in Class

Abstract: In this article we share exploratory findings from a study that captures microaggressions (MAs) in vivo to shed light on how they occur in classrooms. These brief and commonplace indignities communicate derogatory slights and insults toward individuals of underrepresented status contributing to invalidating and hostile learning experiences. Our aim is to expand the ways in which we research and think about MAs in educational settings. Our data are drawn from structured observations of 60 diverse classrooms on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 40 publications
0
52
0
1
Order By: Relevance
“…The same incompleteness can be expected in youth interviews. Collection of observational data is a way to address this limitation (Suárez-Orozco, Casanova, et al, 2015) and should be a third methodological cornerstone of future research. Finally, this study yielded little information about the distinct issues of European American youth and of programs that primarily serve this group, despite their representation in our sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same incompleteness can be expected in youth interviews. Collection of observational data is a way to address this limitation (Suárez-Orozco, Casanova, et al, 2015) and should be a third methodological cornerstone of future research. Finally, this study yielded little information about the distinct issues of European American youth and of programs that primarily serve this group, despite their representation in our sample.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted primarily in schools finds that educators differ greatly in how responsive they are to issues of culture and race (Duncan-Andrade, 2007; Kohli & Solórzano, 2012; Outley & Witt, 2006). Some are resentful or hostile toward youth of color and actively suppress discussion of racial inequalities and injustice; these educators may be most likely to perpetrate microaggressions against youth of color (Kohli & Solórzano, 2012; Suárez-Orozco, Casanova, et al, 2015). Another set of educators is not emotionally invested, may passively follow institutional guidelines, or lacks skills to engage with issues of culture and inequality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…DeAngelis (2009) quotes Sue to say that we need to realise that "Microaggressions hold their power because they are invisible, and therefore they don't allow us to see that our actions and attitudes may be discriminatory" (p. 42). Along with these microaggressions, marginalization is what Suárez-Orozco, et al (2015) note as being elusive, that the perpetrator "recognizes neither his or her position of privilege nor the multiple previous incidents that may have been encountered by the victim of the course of a lifetime" (p. 152).…”
Section: Microagressionsmentioning
confidence: 99%
“…In addition to these faculty perceptions and seemingly deficit views, students continue to have racialized experiences at hSIs, and often within classrooms at hSIs. Suárez-Orozco et al (2015) observed faculty teaching in three hispanic-serving community colleges committing racialized microaggressions within the classroom (in addition to gendered and intersectional microaggressions), with White faculty and those teaching in developmental classrooms committing the greatest number of microaggressions. The microaggressions ranged in type from intelligence-related microaggressions intended to demean the student's intellectual competence to cultural/racial microaggressions, which disparage the race and culture of the victim (Suárez-Orozco et al, 2015).…”
mentioning
confidence: 99%
“…Suárez-Orozco et al (2015) observed faculty teaching in three hispanic-serving community colleges committing racialized microaggressions within the classroom (in addition to gendered and intersectional microaggressions), with White faculty and those teaching in developmental classrooms committing the greatest number of microaggressions. The microaggressions ranged in type from intelligence-related microaggressions intended to demean the student's intellectual competence to cultural/racial microaggressions, which disparage the race and culture of the victim (Suárez-Orozco et al, 2015). Although Suárez-Orozco et al (2015) found that peers also committed these microaggressions, faculty were more likely to be the perpetrators.…”
mentioning
confidence: 99%